Fake news in the time of COVID-19 pandemic:: Case of Algeria - RAMDANE, Abdelmadjid (Journal of Human Sciences, 2021)
This article aims to highlight the phenomenon of "fake news" that feeds the web and social networks and sometimes even the media, on the subject of the pandemic caused by the corona virus COVID-19. These false informations are propagated for different purposes, the article endeavors to determine them.In Algeria, like many other countries in the world, diverse fake news are made-up to coincide with the spread of this virus. These false informations caused confusion among citizens, which required the intervention of the security and judicial authorities.To deal with this subject, which touches  in reality several fields, we applied the descriptive analytical method, by marking up the definitional field of the term "fake news", with an attempt to explain the phenomenon and propose some solutions to remedy it.